IMPLEMENTASI MODEL ADVANCE ORGANIZER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SMP NEGERI 2 LOSARI - SUHERUN, SUHERUN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The aim of this research is to improve the learning outcomes and activity of students at SMP Negeri 2 Losari class IX F Semester I 2022-2023 academic year in learning mathematics by using the Advance Organizer Learning Model in Quadratic Equations topic. The subjects of this research were 31 students in class IX FSMP Negeri 2 Losari for the 2022-2023 academic year. The method used is Classroom Action Research. The data obtained is in the form of test scores for each cycle, supported by teacher observation sheets, student observation sheets and student activity observation sheets. The collaborator in this research was a teacher at SMP Negeri 2 Losari. Data analysis uses comparative descriptive analysis, namely comparing test results before action (initial conditions), test results in the first cycle and test result scores in the second cycle. The research results show that theoretically and empirically, the developed Advance Organizer Learning Model is more effective in increasing the activity and mathematics learning outcomes of class IX F students at SMP Negeri 2 Losari for the 2022-2023 school year in studying mathematical concepts, especially Quadratic Equations. . From the research results, it was revealed that the average achievement in the initial condition (before the action) was 71.96 to 75.00 in cycle I and rose again to 77.59 in cycle II. The initial absorption rate before the action reached 48.39%, became 70.97% in cycle I then rose to 80.65% in cycle II. Learning using the Advanced Organizer Learning Model that was developed turns out to be more effective in increasing students' understanding in studying mathematical concepts. There is also a tendency for students' learning activities to be better. ABSTRAKPenelitian ini bertujuan adalah untuk meningkatkan hasil belajar dan keaktifan peserta didik SMP Negeri 2 Losari kelas IX F Semester I Tahun Pelajaran 2022-2023 dalam pembelajaran matematika dengan menggunakan Model Pembelajaran Advance Organizer pada materi Persamaan Kuadrat. Subjek penelitian ini adalah 31 peserta didik kelas IX F SMP Negeri 2 Losari tahun pelajaran 2022-2023. Metode yang digunakan adalah Penelitian Tindakan Kelas. Data yang diperolah berupa skor hasil tes setiap siklus, ditunjang dengan lembar observasi guru dan lembar observasi peserta didik serta lembar pengamatan keaktifan peserta didik. Kolaborator dalam penelitian ini adalah seorang guru SMP Negeri 2 Losari. Analisis data menggunakan analisis deskriftif komparatif yaitu membandingkan hasil tes sebelum tindakan (kondisi awal), hasil tes pada siklus pertama dan skor hasil tes pada siklus kedua. Hasil penelitian menunjukan bahwa secara teoritik dan empiris melalui Model Pembelajaran Advance Organizer yang dikembangkan ternyata lebih efektif digunakan untuk meningkatkan keaktifan dan hasil belajar matematika peserta didik kelas IX F SMP Negeri 2 Losari tahun pelajaran 2022-2023 dalam mempelajari konsep-konsep matematika khususnya materi Persamaan Kuadrat. Dari hasil penelitian terungkap bahwa capaian rata-rata pada kondisi awal (sebelum tindakan) 71,96 menjadi 75,00 pada siklus I dan naik lagi 77,59 pada siklus II. Tarap serap awal sebelum tindakan mencapai 48,39 %, menjadi 70,97 % pada siklus I kemudian naik menjadi 80,65 % pada siklus II. Pembelajaran menggunakan Model Pembelajaran Advance Organizer yang dikembangkan ternyata lebih efektif digunakan untuk meningkatkan pemahaman peserta didik dalam mempelajari konsep-konsep matematika juga terdapat kecenderungan aktivitas belajar peserta didik lebih baik